68.1k views
3 votes
For f(x) = 5x + 1

A. Find f(7).
B. Find f−1(x).
C. Find f−1(7).
D. Find f( f−1(7)).

Show all work

User Joril
by
4.5k points

2 Answers

4 votes

Answer with step-by-step explanation:

We are given the following function and we are to find f(7), f−1(x), f−1(7) and f( f−1(7)):


f(x) = 5x + 1

A. Find f(7):


f(7)=5(7)+1 = 36

B. Find f'1(x):


y = 5x + 1

Making x the subject to get:


x = (y-1)/(5)


f'1(x) = (x-1)/(5)

C. Find f−1(7):


f'1(7) = \frac {7-1} {5} = \frac {6} {5}

D. Find f( f−1(7)):


x = f ( f^(-1) (7)) \\\\ f^(-1) (7) = \frac{6} {5} \\\\ x = f (\frac {6} {5} ) \\\\ f(\frac {6} {5}) = 5 (\frac {6} {5}) + 1 \\\\ f ( \frac {6} {5}) = 7

User Naresh MG
by
5.6k points
6 votes

Answer:

A.
f(7) = 5(7) + 1\\\\f(7) = 36

B.
f^(-1)(x) = (x - 1)/(5)

C.
f^(-1)(7) =(6)/(5)

D.
f((6)/(5)) = 7

Explanation:

A. To solve the first part of the problem we must replace
x = 7 in the function
f(x) = 5x + 1

So:


f(7) = 5(7) + 1\\\\f(7) = 36

B. In part B we must find the inverse function of
f(x) = 5x + 1

To find the inverse function do
y = f(x)


y = 5x +1

Now clear the variable x.


(y - 1)/(5) = x

Replace x with y.


y = (x - 1)/(5)

Finally


f^(-1)(x) = (x - 1)/(5)

C. Now we take the inverse function found above and replace
x = 7


f^(-1)(7) = (7 - 1)/(5)\\\\f(7) = (6)/(5)

D. Now we substitute
x = f(f^(-1)(7)) in the original function.


x = f( f^(-1)(7))\\\\f^(-1)(7) = (6)/(5)\\\\ x= f((6)/(5) )\\\\f((6)/(5)) = 5((6)/(5)) + 1\\\\f((6)/(5)) = 7

User Jamine
by
5.0k points